Reconfiguration of distribution systems by a modified genetic algorithm - Guimarães, Marcos A. N.; Castro, Carlos A.; Romero, Rubén [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
In this paper a genetic algorithm based reconfiguration method is proposed to minimize the real power losses of distribution systems. The main innovation of this research work is that new types of crossover and mutation operators are proposed, such that the best possible results are obtained, with an acceptable computational effort. The crossover and mutation operators were developed so as to take advantage of the particular characteristics of distribution systems (as the radial topology). Simulation results indicate that the proposed method is very efficient, being able to find excellent configurations, with low computational effort, especially for larger systems. ©2007 IEEE.
Keywords: Distribution systems; Genetic algorithm; Reconfiguration; Algorithms; Genetic algorithms; Electric power distribution